Parsons, James. Interview about growing up in Salmon Cove - Harvey, Katherine A. (1992-) (2017)
Interview with James Parsons conducted by Katherine Harvey. Interview about growing up in Salmon Cove. (00:26) biographic information; (01:15) agriculture/farming; (04:36) making fish; (07:31) potatos; (08:09) pork and beef; (9:00) mail delivery; (10:03) mail delivery; (11:05) school; (12:57) morning chores; (12:57) morning chores; (13:50) gardening; (14:35) gravedigging; (15:10) capelin; (15:50) compost; (16:47) babies/midwives; (17:40) adoption; (18:35) mummers; (20:29) wobbys; (21:38) tricks